2011
DOI: 10.1016/j.jvs.2011.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of spontaneous isolated superior mesenteric artery dissection derived from follow-up after conservative treatment

Abstract: After conservative treatment of SISMAD, we have observed that the majority of patients showed improvement or no change on both angiogram and clinical examination. We believe this observation supports an approach of conservative treatment for patients with SISMAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(157 citation statements)
references
References 18 publications
9
146
2
Order By: Relevance
“…10, 11 It is natural that the mean age was younger in the symptomatic group, as most asymptomatic patients were only diagnosed in the middle of the clinical course because of incidental detection of spontaneous isolated SMA dissection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11 It is natural that the mean age was younger in the symptomatic group, as most asymptomatic patients were only diagnosed in the middle of the clinical course because of incidental detection of spontaneous isolated SMA dissection.…”
Section: Discussionmentioning
confidence: 99%
“…9, 11 Others have stated that the shear stress at the maximum curve of the SMA was the cause of the dissection, based on a hemodynamic simulation study. 19,20 However, our study indicated that the dissection origin was located more proximal to the pancreatic edge or the maximum curve of the SMA, and less than half of patients showed conditions similar to those described by Solis et al 9 and Park et al 19 Thus, the mechanism of spontaneous isolated SMA dissection remains unknown, but may include multiple etiologies.…”
Section: Disclosuresmentioning
confidence: 99%
“…3 In addition, segmental arterial mediolysis and arterial fibroelastic disease might be the fundamental arterial conditions related to this entity. Furthermore, shearing stress around the inferior edge of the pancreas because of differences in SMA fixation, 1.5-3 cm from the SMA origin, and at its maximum curved portion has been suggested as a significant anatomic factor in spontaneous isolated SMA dissection.…”
Section: Ogino Hmentioning
confidence: 99%
“…In general, recent first-line therapy has been conservative management, with or without antithrombotic treatment with antiplatelet and anticoagulant therapy to prevent TL occlusion by stabilizing the intimal flap (Figure, Table). [3][4][5][6][7][8][9][10][11] For a subset of patients with persistent symptoms because of critical bowel ischemia or infarction caused by compression of the TL of the SMA or rupture of the dissecting SMA, endovascular treatment (EVT) with stents or open surgical repair (OSR) is indicated without delay. 11 In the current shift towards EVT for aortic or peripheral arterial lesions, 12 EVT predominates.…”
Section: Ogino Hmentioning
confidence: 99%
“…[18][19] Endovascular or surgical treatment should be performed in cases after failure of conservative treatment, presenting persistent abdominal symptoms, and intestinal ischemia and rupture of the artery. [20][21] In our study, most patients accepted conservative treatment and obtained a favorable outcome except 5 who underwent endovascular intervention.…”
Section: Discussionmentioning
confidence: 99%